Effect of concentrate supplementation during pre-kidding on the productive and reproductive performance of goats raised on Guinea grass (Panicum maximum cv. Tobiatã) pasture - Marques, Raquel Ornelas [UNESP]; Gonçalves, Heraldo Cesar [UNESP]; De Lima Meirelles, Paulo Roberto [UNESP]; Cañizares, Gil Ignácio Lara [UNESP]; De Oliveira, Giuliana Micai [UNESP]; Gomes, Helen Fernanda Barros; Fernandes, Simone [UNESP]; De Oliveira, Aline Aparecida [UNESP]; Brito, Évelyn Prestes [UNESP]; Carmo, Raphaela Felipe [UNESP] (Universidade Estadual de Londrina, 2016)
Sixty goats (20 Alpine, 18 Anglo-Nubian, and 22 crossbred Boer), with average body weight 49.33 ± 1.41 kg, were raised on Panicum maximum cv. Tobiatã pasture with two different levels of concentrate supplementation, 300 (SL30) and 600 g kg-1 (SL60) of the daily requirements, and evaluated from the pre-mating season until an average of 110 days of lactation. Milk controls were performed every 14 days. The following milk production curve parameters were estimated: time to reach peak milk production (TP), peak milk production (PP) and milk production during the first 110 days of lactation (MP). The following milk components were determined: fat, protein, lactose, total solids (TS), defatted dry extract (DDE), urea nitrogen (UN) concentrations, and somatic cell count (SCC). Goat prolificacy and birth weight of the kids were also determined. Breed affected the lactation curve, with Alpine and Anglo-Nubian goats presenting higher TP, PP, and MP. Protein, TS, and DDE concentrations were also affected by breed, being higher for crossbred Boer goats. Milk fat, lactose concentrations, and the log of SCC were affected by the concentrate supplementation level, being higher for SL30, as well as by the breed, with crossbred Boer goats presenting higher fat concentrations and log of SCC, and crossbred Boer and Alpine goats presenting higher lactose concentrations. UN was affected by the stage of lactation. Prolificacy and birth weight were affected by breed and concentrate supplementation level, being higher for Anglo-Nubian and crossbred Boer goats with SL60. Kids from single births presented higher birth weights. The Anglo-Nubian breed presented good milk production and the best body condition, which might indicate the effectiveness of this production system, SL60 supplementation resulted in higher birth weight and prolificacy.
Keywords: Birth weight; Goats; Milk composition; Milk production; Prolificacy